Il mito dell’Età dell’Oro. Immagini e potere nel mondo ellenistico-romano - De Benedictis, Giovanni (O T I V M, 2024)
The myth of the Golden Age was used as an effective propaganda tool by the Hellenistic dynasties and then in Rome from the late republic era. This paper intends to present some points of reference on how and when the myth was transmitted, particularly focusing on the visual culture that gave rise to a complex system of communication through images. The analysis of various iconographic sources highlights the transmission of a motif through a vast repertoire of images that help define a ‘Golden Age landscape’. By examining selected experiences from the Hellenistic world, from Alexander the Great to the Ptolemies, this study underscores the fundamental characteristics of a model that Mark Antony and Augustus would employ during the challenging years leading up to the battle of Actium and beyond. The contribution also lays the groundwork for further investigations into a complex legacy that will fuel the imagination of Neronian culture.